Increased frequency of the S allele of the L-myc oncogene in non-Hodgkin's lymphoma. - Crossen, P. E. (Nature Publishing Group, 1994)
We studied 100 patients with non-Hodgkin's lymphoma, 44 patients with Hodgkin's disease and 100 controls for the prevalence of the EcoRI restriction fragment polymorphism of the L-myc oncogene. No difference in the frequency of the three genotypes (LL, LS, SS) was found between the patient and control groups. However, the S allele was found to occur more frequently in the non-Hodgkin's lymphoma patients (chi 2 = 4.57, P = 0.032). These data confirm an earlier report and suggest that the presence of the S allele is associated with susceptibility to non-Hodgkin's lymphoma.